La responsabilité civile découlant de l'inaction gouvernementale - Brown, L.; Lemieux, Denis (Les Cahiers de droit, 1979)
The proliferation of governmental controls and services has created new aspects of governmental liability. The courts have had recently to decide cases where the claimant alleged that he had been affected by the failure of a public body to act in fulfillment of its responsabilities. Our purpose is, firstly, to indicate the nature and extent of the action for damages resulting from the violation of a statutory duty in English law. We will, then, discuss some recent applications of these principles in Anglo-Canadian and Quebec law.